Predicting the cost of environmental management system adoption: the role of capabilities, resources and ownership structure - Darnall, Nicole; Edwards, Daniel (Strategic Management Journal, 2006)
Abstract This research explores why some facilities accrue greater costs when adopting an environmental management system (EMS) and why costs vary among three different ownership structures. Using survey data of organizations that documented their EMS adoption costs over a 3‐year period, the results show that publicly traded facilities had stronger complementary capabilities prior to EMS adoption and therefore lower adoption costs. By contrast, government facilities and privately owned enterprises had fewer capabilities and accrued higher EMS adoption costs. The development of organizational capabilities and resources therefore appears to be a function of both organizational exploitation of imperfect or incomplete market factors, and the institutional context of these decisions. Copyright © 2006 John Wiley & Sons, Ltd.